Table Tennis Forehand Topspin Shot Ability Level of FIK UNM Students - Sudirman, Akbar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the level of forehand topspin stroke ability in table tennis among FIK UNM students. The location of this research was carried out on the FIKK UNM campus, precisely at the Tenismeja GOR. This research is a type of quantitative descriptive research using survey methods. The sample in this research is students majoring in PJKR FIK UNM who program table tennis courses, totaling 40 people. The test instrument used was a forehand topspin shot test with a midle and baseline target of 10 balls each. Based on the research results, 3 people (7.5%) stated that the table tennis forehand topspin table tennis ability level scores of PJKR FIK UNM students were very poor, 9 people (22.5%) were declared inadequate, 13 people (32.5%) were declared sufficient , 11 people (27.5%) said it was good, and 4 people (10%) said it was very good.